Annealing cycles and the self-organization of functionalized colloids. (4th December 2017) - Dias, Cristóvão S; Araújo, Nuno A M; Telo da Gama, Margarida M
Abstract: The self-assembly of functionalized (patchy) particles with directional interactions into target structures is still a challenge, despite the significant experimental advances in their synthesis. Self-assembly pathways are typically characterized by high energy barriers that hinder access to stable (equilibrium) structures. A possible strategy to tackle this challenge is to perform annealing cycles. By periodically switching on and off the inter-particle bonds, one expects to smooth-out the kinetic pathways and favor the assembly of targeted structures. Preliminary results have shown that the efficiency of annealing cycles depends strongly on their frequency. Here, we study numerically how this frequency-dependence scales with the strength of the directional interactions (size of the patch σ ). We use analytical arguments to show that the scaling results from the statistics of a random walk in configurational space.